Microalgae-mediated brewery wastewater treatment: effect of dilution rate on nutrient removal rates, biomass biochemical composition, and cell physiology - Marchão, Leonilde (2018)
ABSTRACT: Microalgae have been used to remove nitrogen, phosphorus, and chemical oxygen demand (COD) from brewery wastewater (BWW). The microalga Scenedesmus obliquus was grown on BWW, using bubble column photobioreactors that operated under batch and continuous regimes. For the first time, the cell physiological status cell membrane integrity and enzymatic activity was monitored during the microalgae based BWW treatment, using flow cytometry. All the cultivations batch and continuous displayed a proportion of cells with intact membrane > 87%, although the continuous cultivations displayed a lower proportion of cells with enzymatic activity (20-40%) than the batch cultivations (97%). The dilution rate of 0.26 day(-1) was the most favorable condition, since the microalgae cultivation attained the maximum biomass productivity (0.2 g ash-free dry weight day(-1)) and the total nitrogen and COD removal rates were the highest (97 and 74%, respectively), while the phosphorous removal rate was the third (23%).